El melodrama en la narrativa peruana: «Pantaleón y las visitadoras» - Tuesta Figueroa, Teresa Adelaida Aurora (2024)
This article analyzes Pantaleón y las visitadoras (1973) by Mario Vargas Llosa and how the schemes of classic melodrama are developed in the novel in relation to the structure, purpose, themes and construction of characters. Our research observes how the resource of irony enables the manifestation of the pathos of the relationships between the characters, built with manichean overtones and complex features, which otherwise would not reach fictionality, likewise, the common theme of family roots and dishonor.